Identification Of A Cd36 Scavenger Receptor Binding Peptide Using A 12-Mer Peptide M13 Phage Display Library - Ayob, Muhammad Salahuddin (2018)
CD36 is a class B scavenger receptor which is involved significantly in the uptake of oxidised low-density lipoprotein (oxLDL). Accumulation of lipid contributes to foam cells formation, which is the precursor to atherosclerosis plaque. The aim of this study was to identify specific peptides which interact and bind to CD36 as it has the potential to be developed into a peptide inhibitor and as a molecular intervention in treating athero-inflammatory disorders. In this study, 12-mer Ph.D-12TM Phage Display Peptide Library, which was validated in streptavidin panning, was used in selection against CD36. CD36-binding assay was performed by incubating the selected phages with two CD36-expressing cell lines, CHO-CD36 and U937 and a CD36-non expressing cell line, HeLa, followed by anti-M13 phage-PE and mouse IgG2b-PE isotype antibodies staining.